Una alternativa tripartida: la varietat tradicional, la varietat estàndard catalana o la varietat estàndard espanyola - Ponsoda, Joan J.; Segura, Carles (Caplletra. Revista Internacional de Filologia, 1996)
The purpose of this paper is to show how the Catalan spoken in the south Valencian region is reacting to the effects of the linguistic normalization process that was initiated more than ten years ago. Basically, this process concentrated on two areas: on the one hand, education, where Catalan is present either as a compulsory subject, or as the language in which the whole teaching takes place; on the other hand, the spreading of several mass media which more or less use the language. We shall try to describe a few linguistic phenomena, phonetic as well as morphologic and lexical, through a survey carried out among various age groups and, in the case of small children, considering their school situation concerning Catalan and their family language. In this way, we shall grasp the predictable generational differences, the origin of which we shall try to find out, especially in order to relate the fact to the new sociolinguistic situation.